The most common aspects of crime in the old neighborhoods from the inhabitants’ perspective - HAMANI, Hazem; HADJ KHELLOUF, Fatima Zohra (Journal of Human Sciences, 2025)
This study aims at identifying the most common aspects of crime in the old neighborhoods from the inhabitants’ perspective. In so doing, we used the descriptive method and chose a random sample of 20 inhabitants from La Cité Columbia in Tedjnanet, Mila, to whom we administered a questionnaire. Findings show that the most common aspects of crime in such neighbors include the gangsters’ crimes, drug dealing and consumption, armed fights, and burning others’ cars.